Health and Safety Issues in Selected Nigerian Medium-Sized Manufacturing Firms - Akinbode, James; Ebeloku, Ademola; Unuafe, Francisca; Akintunde-Adeyi, Julianah (Universitas Airlangga, 2024)
Introduction: Medium-sized firms around the world are confronted with several challenges which have continued to hamper their growth chances. One of these issues is lack of global best practices in health and safety. This issue is pronounced among medium-sized manufacturing firms in Nigeria. It was against this backdrop that the study investigated the state of health and safety issues in selected Nigerian medium-sized manufacturing firms. Methods: Survey research design was adopted involving leading medium-sized manufacturing firms in Nigeria. Issues pertaining to health and safety were identified and analyzed. Data were gathered through administration of structured questionnaire and observation check list. Analyses were presented through appropriate statistical means. Results: Relatively secured work environment, workers’ exposure to hazard, absence and inadequate protective devices for workers, archaic fire system infrastructure, lack of insurance cover for workers, irregular health and safety training, inconsistent compliance to health and safety rules were found as the issues in selected Nigerian medium-sized manufacturing firms operating in Nigeria. Conclusion: Health and safety issues is a cog in the wheel of Nigerian medium-sized manufacturing firms. It is imperative to address this issue to strengthen the operations of the industry. The promotion and practice of hygienic health system and safety culture by workers and management must be the way of life in manufacturing firms.